Характеристика культуры клеток надпочечников новорожденных поросят, полученной из криоконсервированных фрагментов ткани - Сидоренко, О.С.; Божок, Г.А.; Легач, Е.И.; Бондаренко, Т.П. (Вісник проблем біології і медицини. 2013;4(1):95-9., 2013)
изучены культуры клеток надпочечников (ккН) новорожденных поросят, полученных из фрагментов ткани, криоконсервированных под защитой 10% ДМСо со скоростью охлаждения 0,3°/мин. В динамике развития такой ккН отмечаются этапы, характерные для культур, полученных из свежевыделенных фрагментов ткани: наблюдается формирование фибробластоподобного монослоя, затем формирование цитосфер на монослое и миграция из них клеток нейроноподобной морфологии. С помощью иммуноцитохимического окрашивания было показано, что нейроноподобные клетки экспрессируют β – III -тубулин. используемый режим криоконсервирования оказывает селективный эффект, который проявляется в увеличении количества цитосфер при культивировании. ____________________________________________________ Вивчено культури клітин наднирників (ккН) новонароджених поросят, отриманих з фрагментів тканини, кріоконсервованих під захистом 10% ДМСо зі швидкістю охолодження 0,3°/хв. У динаміці розвитку такої ккН відзначаються етапи, характерні для культур, отриманих зі свіжовиділених фрагментів тканини: спостерігається формування фібробластоподібного моношару, потім формування цитосфер на моношарі та міграція з них клітин нейроноподібної морфології. За допомогою імуноцитохімічного аналізу було показано, що нейроноподібні клітини експресують β – III – тубулін. режим кріоконсервування, що застосовувався, надає селективний ефект, який проявляється у збільшенні кількості цитосфер при культивуванні. _____________________________________________________________________ Adrenal cell culture (ACC) is widely used for the study of neuronal differentiation as well as transdifferentiation. Cryopreservation as a method of long-term storage of biological material influences on the structural and functional features of the frozen samples, and can significantly affect the behavior and properties of cells during their subsequent cultivation. Thus, we have previously shown that cryopreservation of newborn piglets adrenal tissue fragments with a cooling rate higher than 1°/min can not maintain adhesion properties of the cells. As a result, these cells do not form a monolayer and cytospheres in the culture that is typical for cells derived from unfrozen (native) tissue fragments. In this paper the fragments were frozen with a cooling rate of 0,3°/min to -70°C, followed by plunging into the liquid nitrogen. The cryoprotective medium based in medium DMEM/F12 with 10% dimethyl sulfoxide (DMSO). After thawing and washing fragments the cell suspension was obtained by enzymatic method using collagenase and deoxyribonuclease, and cells were cultured in DMEM/F12 medium supplemented with 10% fetal calf serum. The dynamic of ACC obtained from cryopreserved tissue fragments is similar to that of ACC obtained from freshly isolated tissue fragments: there is the formation of a fibroblast-like monolayer, followed by the formation of cytospheres on the monolayer and the migration of cells with neuron-like morphology. It should be noted that the increase of cytosphere number were observed in ACC derived from cryopreserved tissue fragments (1461±199 cytospheres per 1 million cells vs. 404±160 cytospheres per 1 million cells in ACC obtained from freshly isolated tissue fragments) as well as a proportional reduction of the average cytosphere diameter (66±24 µm vs. 240±69 µm in ACC obtained from freshly isolated tissue fragments). Despite the reduction of cytosphere diameter in ACCs derived from cryopreserved tissue fragments, they retained cell population capable of neuronal differentiation. The immunocytochemical assay has demonstrated that neuron-like cells migrating from the cytosphere express neurospecific β – III-tubulin. Thus cryopreservation of newborn piglets adrenal tissue fragments with cooling rate of 0,3°/min in the medium with 10% DMSO allows to preserve cells capable of forming confluent monolayer, cytospheres as well as cells capable of neuronal differentiation. Such regime of cryopreservation has a selective effect that consist in increasing of cytosphere number under cultivation.
Характеристика культури клітин наднирників новонароджених поросят, отриманої з кріоконсервованих фрагментів тканини
Characteristics of newborn piglets adrenal cell culture obtained from cryopreserved tissue fragments
Сидоренко ОС, Божок ГА, Легач ЕИ, Бондаренко ТП. Характеристика культуры клеток надпочечников новорожденных поросят, полученной из криоконсервированных фрагментов ткани. Вісник проблем біології і медицини. 2013;4(1):95-9.
Keywords: культура клеток надпочечников; криоконсервирование; цитосферы; нейрональная дифференцировка; Beta-III-tubulin; Beta-III-тубулин; дифференцировка; надпочечники поросят